Monokulturalisme dalam Tayangan Web Series Animasi Anak Nussa - Muhammad Alzaki Tristi; Rani Attiqah Gusbet (Jurnal Media dan Komunikasi Indonesia, 2024)
The objective of this study is to demonstrate how the concepts of monoculturalism are evident in the Nussa children's web series animations. Utilizing a qualitative approach, the research involved content analysis of five specific episodes from the Nussa Official YouTube channel. The analysis employed a semiotic approach to uncover both explicit and implicit meanings. The study's framework for monoculturalism is based on the concepts outlined in "Golden Truth" from the publication "The Danger of Monoculturalism in the XXI Century" and Indonesia's Broadcasting Law No. 32/2002, particularly Articles (2) and (36). These concepts highlight four key points: (1) The prevalence of a homogeneous society; (2) An inadequate portrayal of tolerance; (3) Insufficient diversity; and (4) A lack of communicative interaction and representation through cultural symbols. The findings reveal that the Nussa animated content does not adequately depict societal and cultural variety in each episode. Additionally, the Nussa production team fails to incorporate dialogues and symbols that reflect Indonesia's rich cultural diversity. In conclusion, it is recommended that future episodes of Nussa's animated web series should incorporate greater diversity.